Incidence and risk factors for postoperative nosocomial pneumonia in elderly patients with hip fractures: A single-center study - Tong, Xiao; Ci, Caizhe; Chen, Jia; Sun, Minghong; Zhao, Hongbo; Wei, Haiqiang; Yu, Tieqiang; Wang, Hui; Yang, Weixin (Frontiers in Surgery, 2023)
Objective Postoperative nosocomial pneumonia is a terrible complication, especially for elderly patients. This study attempts to investigate the incidence and risk factors for postoperative nosocomial pneumonia and its influence on hospitalization stay in elderly patients with hip fractures. Methods: This study retrospectively retrieved hospitalization records of patients who presented a hip fracture and underwent surgeries in our institution between January 2014 and December 2021. Postoperative new-onset pneumonia was determined in accordance with discharge diagnosis. Multivariate logistic regression analysis was performed to identify the associated risk factors with pneumonia, and its influence on total hospitalization stay or postoperative hospitalization stay was investigated by multivariate linear regression analyses. Results: Totally, 808 patients were included, among whom 54 developed a pneumonia representing the incidence rate of 6.7% (95%CI, 5.0%-8.4%). Six factors were identified as independently associated with pneumonia, including advanced age (OR, 1.50 for each 10-year increment), history of chronic respiratory disease (OR, 4.61), preoperative DVT (OR, 3.51), preoperative delay to operation (OR, 1.07 for each day), surgical duration ≥120 minutes (OR, 4.03) and arthroplasty procedure (OR, 4,39). When adjusted for above confounders, pneumonia was significantly positively associated with total hospitalization stay (standardized coefficient, 0.110; p<0.001) and postoperative hospitalization stay (standardized coefficient, 0.139; p<0.001). Conclusions: This study identified multiple factors associated with postoperative pneumonia and its influence on prolonging hospitalization stay, which would facilitate preventive targeted intervention into implementation for individuals with different risk profiles.